2002
DOI: 10.1111/1467-8462.00256
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Analysis of the Determinants of Employment and Labour Force Participation: Indigenous and Non‐Indigenous Australians, 1981 to 1996

Abstract: two anonymous referees for comments on an earlier draft. The professionalism of the Australian Bureau of Statistics Consultancy Unit in estimating the synthetic panel models is greatly appreciated. All remaining errors and omissions are the sole responsibility of the authors. The views expressed in this article do not necessarily reflect those of the Australian Institute of Family Studies. AbstractData from the 1981, 1986, 1991 and 1996 cen-suses are used to construct a synthetic panel which is used to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…A 'basic' specification including core control variables similar to Gray and Hunter (1999), corresponding to the variables available in the Census data is estimated as well (see Kalb et al, 2012b). 17 Compared to the specification in Table 2, the pseudo R 2 value is considerably lower, indicating that less of the variation can be explained by this basic model.…”
Section: Regression Results For the Indigenousmentioning
confidence: 99%
“…A 'basic' specification including core control variables similar to Gray and Hunter (1999), corresponding to the variables available in the Census data is estimated as well (see Kalb et al, 2012b). 17 Compared to the specification in Table 2, the pseudo R 2 value is considerably lower, indicating that less of the variation can be explained by this basic model.…”
Section: Regression Results For the Indigenousmentioning
confidence: 99%
“…And the academic community has profited by the findings of studies and investigations that have given attention to the HRM practices and policies employed by Australian mining companies (Moore & Gardner, 2004;Nadkarni & Stening, 1989). In addition to the technical business of operating the mining facilities, an intensification of community engagement has potential to foster improved socioeconomic conditions of Indigenous people in remote regions (Barker, 2006;Gray & Hunter, 2002). The social inclusion of regional communities provides an opportunity for mining companies to positively address the persistent low employment rates of Indigenous Australians.…”
Section: Mining Sectormentioning
confidence: 99%
“…On the one hand the government policies in empowering Indigenous population has not been successful over the past decades (Arthur, 2002;Gray & Hunter, 2002;Pholi, Black, & Richards, 2009), while on the other hand multinational corporations are unable to leverage contemporary conceptual knowledge or practical case examples to their advantage in linking with an increasingly young and marginalized Aboriginal population in remote regions of Australia. Successive governments in Australia have struggled to achieve socioeconomic uplifting of Indigenous citizens (Altman, Biddie, & Hunter, 2005;Cook, 2008;Brereton & Parmenter, 2008;Gray & Hunter, 2002). Furthermore, multinational mining companies are finding it extremely difficult to attract, develop, retain, and obtain organizational commitment of junior-level managers to move to remote regions of Australia and adopt a very different lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Supported training has been considered a strategy to replace despair with hope, to remove fear of the unknown, and to build confidence, thereby helping people who have relied on income support for prolonged periods of time take their first, tentative steps up "the staircase of opportunity" (Pearson, 2008, p. 1). Although the need for both education and training has been identified in employment policies of successive national governments since 1975 (Australian Government Commission of Inquiry into Poverty, 1975;Daly, 1993;Gray & Hunter, 2002;Hunter, 1977) and has been reinforced by some Indigenous leaders, the employment gap has neither narrowed nor closed. However, the most recent Australian Prime Minister's Closing the Gap report identified that for those Indigenous Australians with higher levels of education there is virtually no employment gap (Australian Government, 2016).…”
mentioning
confidence: 99%